Distribution of the Mesozooplankton Community in the Western Ross Sea Region Marine Protected Area During Late Summer Bloom - Kim, Sung Hoon; Kim, Bo Kyung; Lee, Boyeon; Son, Wuju; Jo, Naeun; Lee, Junbeom; Lee, Sang Heon; Ha, Sun-Yong; Kim, Jeong-Hoon; La, Hyoung Sul (Frontiers in Marine Science, 2022)
The spatio-temporal distributions of the mesozooplankton community were investigated in the western Ross Sea region marine protected area (RSR MPA). Mesozooplankton surveys were conducted to address the essential environmental factors to control the mesozooplankton community structure in February 2018, January 2019, and March 2020. Our results showed that the mesozooplankton community of the western RSR MPA could be affected by the various ecological factors, depending on temporal and spatial variations. The community structure in 2018 could be distinguished by chlorophyll-a (Chl-a) concentration during the summer bloom phase in the late summer. Taxa observed in 2019 were divided into four significantly different groups according to the body size of the community composition. This differentiation would be derived from feeding pressure, inducing a trophic cascade. Taxa in 2020 were separated into five different groups according to the temperature while the water temperature decreased and sea ice covered the whole continental shelf in the Ross Sea. Additionally, comparing the three interannual surveys, even though the communities were well clustered according to the survey period, we see that the continental shelf groups were quite dissimilar each other despite overlapping geographically. Taken all together, the mesozooplankton community of the western RSR MPA was altered according to several ecological factors, such as temperature, Chl-a concentration, and feed pressure. The occurrence of summer blooms and the decline in water temperature mainly regulated the mesozooplankton community structure in the late summer.